2015
DOI: 10.18632/oncotarget.6777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pravastatin on the survival of patients with advanced gastric cancer

Abstract: ObjectivesA fluoropyrimidine plus cisplatin combined with surgery is standard first-line treatment for advanced gastric cancer. We evaluated the effect of pravastatin on overall survival in patients with advanced gastric cancer in a prospective cohort study.MethodsAt the time of surgery, we assigned 60 patients with advanced gastric cancer (stage III or IV) to receive standard first-line treatment (control group) or standard first-line treatment plus pravastatin at a dose of 40 mg once daily (pravastatin group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This indicates hope as a possible adjuvant therapy agent for GCa patients. There has been some success of using statins in preclinical GCa models , but most clinical trials have failed . In this study, we found that HMGCR is not a positive promoter for GCa progression.…”
Section: Discussionmentioning
confidence: 61%
“…This indicates hope as a possible adjuvant therapy agent for GCa patients. There has been some success of using statins in preclinical GCa models , but most clinical trials have failed . In this study, we found that HMGCR is not a positive promoter for GCa progression.…”
Section: Discussionmentioning
confidence: 61%
“…A 2014 Korean phase three trial randomly allocated 244 Stage 4 gastric patients to simvastatin 40 mg daily or placebo finding little evidence of difference in progression‐free survival in the simvastatin group compared with placebo (HR 0.93; 95% CI, 0.68‐1.26) . Similarly, a nonrandomised prospective study from Spain found no difference in survival for Stage 3 or 4 patients with gastric cancer, 20 of whom were allocated to receive pravastatin and 40 to placebo . A Korean observational study investigated recurrence‐free survival and all‐cause mortality in 241 patients with Stage 2 and 3 gastric cancer undergoing radical gastrectomy.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, several observational studies showed reductions in gastric cancer risk with statin use . Four studies have investigated statin use postgastric cancer diagnosis and survival; however, these were not population‐based, limited by small‐size (largest study contained 244 patients) and were generally conducted in specific subgroups of gastric cancer patients (for instance, Stage 4 patients). Furthermore, results were conflicting, with one study observing an 83% reduction in all‐cause mortality with 6 months of statin use whilst others observed little evidence of improved outcomes …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations